Impact of psychosocial factors on academic performance of nursing students in Thailand - Paul Ratanasiripong; Chiachih DC Wang; Nop Ratanasiripong; Suda Hanklang; Duangrat Kathalae; Pornlert Chumchai (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this study is to investigate the psychosocial factors that impact the academic performance of nursing students. Design/methodology/approach - A cross-sectional study was conducted with 767 nursing students from three nursing colleges in Thailand. Instruments included Counseling Center Assessment for Psychological Symptoms and Rosenberg Self-Esteem Scale. Path model analyses with the maximum likelihood method were utilized to examine the proposed model. Model fit was estimated using multiple indexes, including chi-square/df ratio (χ2/df), comparative fit index (CFI), Tucker-Lewis index (TLI) and the root mean square error of approximation (RMSEA). Findings - Results indicated that family distress, emotional negativity, self-esteem and substance use were factors that related to nursing students' academic performance. Findings of path analyses indicated that the model demonstrated good fit: χ2 (2, N = 767) = 3.11, p = 0.48; χ2/df = 1.56; CFI = 1.00; TLI = 0.99; RMSEA = 0.027, (90% CI = [0.000, 0.082], PCLOSE = 0.68). Originality/value - While prior research has examined some facets leading to academic success for nursing students, psychosocial factors have not received adequate attention. This study presents a model of family and individual psychosocial factors that impact academic performance of nursing students along with recommendations to help improve their well-being.